Prevalence of renal tubular dysfunction in beta thalassemia minor in shiraz - Ali Moradi Nakhodcheri; Mohammad Ali Yaghut (Fasa University of Medical Sciences, 2011)
Background & objective: β-Thalassemia minor is an asymptomatic hereditary disease. The first study on the relation of renal tubular dysfunction and β-thalassemia minor was performed in 2002 but those studies seem inadequate.The main goal of this study is through evaluation of renal tubular function in 100 patients with thalassemia minor. Materials & Methods: 100 patients with β- thalassemia which confirmed by hemoglobin electrophoresis and CBC as well as RBC indices were studied.14 out of 100 cases exit because of Urinary Tract Infection, diabetes mellitus or hypertension.Complete chemistry profile was performed on serum and urine of all reminder 86 patients (46 female and 40 male). Patients classified into two groups: β-thalassemia minor with anemia and without anemia. Another control group include 50 healthy individuals also considered.Then data analyzed by proper statistical methods. Results: 20 out of 86 reminder cases e.g. 24% showed at least one index of renal tubular dysfunction.58% of patients was been anemic and 42% non anemic. The most prominent tubular dysfunction was seen in a 29 years old lady with glucosuria and without anemia. conclusion: β-Thalassemia minor is common in Iran specially in Fars province. This study revealed significant renal tubular dysfunction in patient with β-thalassemia minor. So it is necessary to check out thalassemic patients for renal function tests periodically. Key words: β-thalassemia, minor,renal tubular dysfunction